Acceptance Analysis of School Procurement System (SIPLah) Using the UMEGA Model: Based on the Perspective of Users in Education Units - Meilinda Puji Pamungkas; Wendy Nur Falaq; Dana Indra Sensuse (Proceeding of International Conference on Information Science and Technology Innovation (ICoSTEC), 2022)
The Work Unit for Procurement (UKPBJ) of the Indonesian Ministry of Education and Culture has developed a Procurement Information System in Schools (SIPLah) to create effectiveness, efficiency, transparency, and accountability of the procurement ecosystem in education units. 103,619 education units have used SIPLah, this achievement has not met the target of 220,283 schools in 2019 which has increased to 442,960 education units in 2020. The level of user acceptance has a significant influence on achieving the target number of users, but UKPBJ has never conducted research related to this factor. As a result, user acceptance has not become a reference in determining strategies in the socialization and development of SIPLah. This study aims to determine the factors that influence the adoption of SIPLah from the user's perspective in educational units using the Unified Model of E-Government Adoption (UMEGA). In this exploratory research, the perceived risk variable on UMEGA which in the hypothesis has a negative effect, be changed to perceived security so that it has a positive effect and is in line with other hypotheses. There were 150 valid respondents who were analyzed statistically using PLS-SEM with SmartPLS 3.0 software. The results of the study can be concluded that factors of performance expectancy, social influence, facilitating conditions, perceived security, and attitude are factors that must be considered by UKPBJ in determining strategies to socialize and develop SIPLah, because these factors have a significant positive impact on user intentions in education unit to adopt SIPLah.